Detection of Aedes albopictus pre-imaginal stages in brackish water habitats in Brunei Darussalam - Fakhriedzwan Hj, I.; Usman, A.; Surendran, S.N.; Ramasamy, R. (My University, 2013)
The mosquitoes Aedes (Stegomyia) albopictus Skuse and Aedes (Stegomyia) aegypti (Linnaeus) are vectors of dengue, chikungunya, and other arboviruses and are widely regarded to undergo pre-imaginal development only in freshwater habitats. As there is no vaccine or specific drug for dengue, eliminating or larviciding the freshwater habitats of the vectors are important strategies for controlling dengue worldwide. However, such measures have failed to eradicate dengue from Brunei Darussalam, with an incidence of 73 cases per 100,000 persons in 2010, and other Southeast Asian countries with extensive coastal areas (Arima and Matsui 2011, Chun et al. 2007). They also did not prevent recent epidemics of chikungunya in Asia (Lobo et al. 2011, Surendran et al. 2007, Weaver and Reisen 2010). Two-fifths of the world’s population is now at risk from dengue, which shows an increasing incidence and global spread. Aedes aegypti and Ae. albopictus were recently shown to oviposit and undergo pre-imaginal development in brackish water (fresh, brackish, and saline waters are defined as containing <0.5, 0.5 to 30, and >30 parts per thousand (ppt) salt, respectively) in discarded plastic and glass containers, abandoned boats, and wells in coastal areas of Sri Lanka in South Asia (Ramasamy et al. 2011, Surendran et al. 2012). Such brackish water habitats are potential sources of vectors that may contribute to the transmission of dengue and other arboviral diseases in coastal areas. We therefore investigated the possible presence of Ae. aegypti and Ae. albopictus larvae in brackish water collections along the South China Sea coast of Brunei Darussalam, a dengue-endemic Southeast Asian country where dengue is known to occur in coastal areas (Chun et al. 2007